2002
DOI: 10.1590/s1519-566x2002000300015
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e Reprodução do Predador Podisus distinctus (Stal) (Heteroptera: Pentatomidae) Frente a Doses Subletais de Permetrina

Abstract: Development and Reproduction of the Predator Podisus distinctus (Stal) (Heteroptera: Pentatomidae)Exposed to Sublethal Doses of Permethrin ABSTRACT -Development and reproduction were studied in the predator Podisus distinctus (Stal) subjected to sublethal doses of the insecticide permethrin under laboratory conditions. Third instar nymphs were subjected to topical application of permethrin at the doses of 0, 0.0172, 0.172, 1.72, 17.2 e 172 ppb. The only parameter statisticaly different was egg viability. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Ramachandran et al 29 found that low doses of azadirachtin increased survival, larval weight and rate of development of the red flour beetle Tribolium castaneum (Herbst). Similar effects of permethrin on the stinkbug Podisus distinctus (Stål)30 and of several insecticides on the house cricket Acheta domesticus L31 have been documented. This is the first report of an insecticide having a hormetic effect on L decemlineata development, and is also the first report of benzoylphenyl urea induced hormesis in an insect.…”
Section: Resultsmentioning
confidence: 62%
“…Ramachandran et al 29 found that low doses of azadirachtin increased survival, larval weight and rate of development of the red flour beetle Tribolium castaneum (Herbst). Similar effects of permethrin on the stinkbug Podisus distinctus (Stål)30 and of several insecticides on the house cricket Acheta domesticus L31 have been documented. This is the first report of an insecticide having a hormetic effect on L decemlineata development, and is also the first report of benzoylphenyl urea induced hormesis in an insect.…”
Section: Resultsmentioning
confidence: 62%
“…The big‐eyed bug Geocoris spp. and the spined soldier bugs Podisus distinctus and Supputius cinceticeps were subsequently studied . Hormesis studies on natural enemies are more common with insect predators than parasitoids.…”
Section: Hormesis In Arthropodsmentioning
confidence: 99%
“…However, the pre-reproductive period of three coccinelid species were not affected by the exposure to copper sulfate fungicide (Michaud and Grant, 2003). The oviposition period of the P. maculiventris females was not affected by the sublethal doses of diflubenzuron and pyriproxyfen (De Clercq et al, 1995) found for other Pentatomidae predators Magalhães et al, 2002). Pesticides can have favorable effects on the biotic potential of arthropods (Ripper, 1956) even indirectly with low doses (Calabrese and Baldwin, 2000).…”
Section: Sublethal Effects On Development and Survival Of The Immaturmentioning
confidence: 87%
“…Pest species could have less longevity after exposure to sublethal doses of insecticides (Stewart and Philogene, 1983) but Tetranychus urticae Koch (Acari: Tetranychidae) had greater longevity after ingestion of imidacloprid (James and Price, 2002). Sublethal doses of permethrin did not affect the longevity of P. distinctus adults after topical exposition (Magalhães et al, 2002). This suggested that the hormesis phenomenon could occur even without an impact on other biotic characteristic.…”
Section: Sublethal Effects On Development and Survival Of The Immaturmentioning
confidence: 99%